MEDIA PEMBELAJARAN SERVIS DAN REPARASI MOBIL BERBASIS SISTEM PAKAR (Studi Kasus di SMK Kyai Ageng Pandanaran) - Indrawan Nagasus; Fujiama Diapoldo Silalahi (Elkom : Jurnal Elektronika dan Komputer, 2018)
SMK Kyai Ageng Pandanaran Semarang is one of the private vocational high school that want to improve quality of teaching and learning to produce quality graduates. During these teaching and learning methods that are used less than maximum, students are easily saturated, study time is limited and there are no facilities for new teachers to learn service and auto repair material efficiently. The authors develop a learning media services and auto repair expert system based that aims to resolve the issue. Learning media is developed by prototype approach. Expert system technology advanced trace method is applied into the learning media through the facilities of diagnosis and troubleshooting to help new teachers and student learning to identify the damage automobile. Database can be managed and updated by senior teachers by utilizing the MySQL database and PHP programming language. In addition, this learning media also features video demonstration of the *.swf file and the theoretical material in the form of a *.pdf file. The results of the development has produced a new system of web-based expert system as a supplement learning media services and auto repair in the process of teaching and learning activities.